Analisis Unsur Visual dan Makna Ekspresif pada Karya Gambar Siswa Sekolah Dasar Bertema “Lingkungan Sekitarku” - Niken Ria Nastiti; Andaryani, Eka Titi; Setiawan, Deni (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to describe the application of visual elements and interpret the expressive meaning in elementary school students' artwork themed "My Surrounding Environment." The approach used is descriptive qualitative with visual analysis techniques. The research subjects consist of ten works from fourth-grade students, analyzed based on four main aspects: line, shape, color, and composition. Data were collected through documentation of the artwork, observation of the learning activities, and reflective notes from the teacher. The results show that lines are used by the children as a means of expressing emotions and movement; geometric and organic shapes reflect symbolic representations of their visual experiences; bright colors such as green, blue, and yellow indicate positive feelings toward the environment; and simple compositions show an intuitive balance typical of elementary school age. Expressively, the students' artwork conveys values such as cooperation, responsibility, and care for nature. The findings emphasize that visual arts education in elementary schools plays a crucial role in developing visual literacy, ecological awareness, and character formation through a creative, reflective, and contextual process.